Addressing the refugee crisis through the lens of Islamic international law - Elshobake, Mohammed R. M. (Malaysian Bar, 2024)
This paper aims to examine the current refugee crisis through the lens of Islamic international law. Refugee crisis is one of the most urgent humanitarian challenges of our time and it involves the majority of Muslim nations worldwide. Critical analysis and library research are used to uncover the issue. It is found that Islamic principles like human dignity (Karamah), preservation of life (Hifz Al-Nafs), and communal responsibility (Ukhuwwah) are align to the modern international refugee law in its ethical, moral and humane treatment of refugees and the importance of global cooperation to curb the issue especially among the Muslim countries. The paper also discusses the political, social, and economic impact of refugees in the host countries and relevant Islamic principles to combat them,such as balance and equity (Mizan, Wasatiyyah), shared responsibility (Takaful), implementing gradual changes (Tadarruj), and prioritising security and welfare (Maslahah). It is concluded that Islamic principles can enrich and complement the modern international refugee law to develop kinder, fairer, and more sustainable answers to the global refugee challenge. Ultimately, the paper seeks to preserve the lives and well-being of refugees and to address their issue from the perspective of Islamic international law.